KINANTHROPOMETRICAL CHARACTERISTICS OF BRAZILIAN AND PAN AMERICAN MALE BEACH VOLLEYBALL PLAYERS (Fiep Bulletin - online, 2014)
The aim of this research is to compare anthropometry, body composition (BC) and somatotype (S) of the Brazilian and Pan American male beach volleyball elite. Methodology. The sample consists of 16 players: eight (08) Brazilian players (BR) and eight (08) Pan American players. The somatotype was calculated by Heath and Carter technique. The sum of four skinfolds (biceps, triceps, subscapular and suprailiac) was used to the body fat percentage calculation (BF%) by Siri's equation. It was used a multivariate analysis of variance (MANOVA) and significance 5%. Results. It was found height 194.65±5.1cm (BR) and 190.70±3.9cm (PAN); body mass 90.04±9.0kg (BR) and 89.85±7.2kg (PAN); body fat (%) 13.41±2.6 (BR) and 15.04±1.2 (PAN); fat mass 12.17±3.1kg (BR) and 13.87±1.8kg (PAN) fat free mass 77.87±7.1kg (BR) e 75.98±6.4kg (PAN). It was found significant differences (p=0.007) in the skinfold triceps. The BR players' somatotype was classified in ectomorphic mesomorph (2.5-4.1-3.3) and the PAN in endomorphic mesomorph (3.1-4.5-2.6). It was concluded that the BR and PAN beach volleyball athletes did not present statistically significant differences in the anthropometrical variables and corporal composition, except for the skinfold triceps. Concerning the somatotype, the PAN athletes were bigger in endomorphy. However, the differences among elite athletes may also be associated with the variables which were not investigated in this study such as technical ability, tactics, physical fitness and psychological preparation.
Keywords: Beach Volleyball; Somatotype; Performance